Practical Solutions for Healthcare Worker Protection During the COVID-19 Pandemic Response in the Ambulatory, Emergency, and Inpatient Settings. Issue 11 (November 2020) - Kraus, Anthony; Awoniyi, Oluwafunbi; AlMalki, Yousef; Bardeesi, Adham Sameer A.; Edwards, Bridget; AlHajjaj, Fahad; Alossaimi, Bader; Benham, Todd; Bortolin, Michalengelo; Cattamanchi, Srihari; Court, Michael; Groves, John; et al.
Abstract : Objective: Protecting healthcare workers is an essential component of a successful response to the COVID-19 pandemic. The resource intensive nature of infectious disease protection, budgetary constraints, and global shortages of personal protective equipment (PPE) make this a daunting task. Practical, easily implemented strategies for healthcare workers (HCW) protection are needed. Methods: We cross-reference the "Systems, Space, Staff, and Stuff" paradigm from disaster management and the "Hierarchy of Controls" approach to infection prevention from the Center for Disease Control and Prevention (CDC) to generate a narrative overview of worker protection strategies relevant to COVID-19. Results: Alternative types of PPE, management of hazards, and reorganizing how people work can optimize HCWs protection. Conclusions: A comprehensive PPE strategy can utilize the "systems, space, staff, stuff" paradigm of disaster management to identify new or underutilized solutions to HCWs protection.